Ukraine’s Air Defence in the Russian-Ukrainian War (2022–2024): Progress in Regression - Kharuk, Andrij (Faces of War, 2024)
Russia’s full-scale aggression against Ukraine, which began on February 24, 2022, posed serious challenges to the Ukrainian air defence system. Its traditional instruments – long- and medium-range anti-aircraft missile systems (S-300, Buk-M1) and fighter aircraft (MiG-29, Su-27) – did not always prove effective in the new conditions. It was necessary to repel mass attacks from cruise missiles which were characterised by having a small deflection area and the ability to fly at lowaltitude targets. In September 2022, the Russians started to use numerous attack drones called Shaheds, which meant that the Ukrainian air defence had to adapt quickly to the new threat. In order to combat these missiles, mobile fire groups with machine guns and MANPADS on pickup trucks began to be used, which quickly advanced towards the enemy attack. The equipment used by these mobile fire groups was gradually improved. One example was from the Czech Republic, where Viktor sets were created. These consisted of twin-barrelled machine guns from the 1940s combined with thermal imaging cameras and mounted on pick-up trucks. German FlakPz Gepard self-propelled anti-aircraft guns transferred by partner countries also proved very effective. In NATO countries, this equipment was considered obsolete in the 1990s, but between 2022–2024 in Ukraine, it effectively destroyed UAVs and cruise missiles. Light training and sports aircraft, provisionally armed with machine guns and using tactics from World War I, have been successfully used to fight unmanned aerial vehicles. These examples show that even in regression, as highlighted by a return to air defence measures from previous decades, progress can be made to adapt to new threats from the air. This article aims to present the unconventional air defence measures used by the Armed Forces of Ukraine to eliminate the threat posed by Russian aerial attack assets.